Hexane isomers separation on an isoreticular series of microporous Zr carboxylate metal organic frameworks - Henrique, Adriano (2018)
A series of isoreticular Zr carboxylate MOFs, MIL-140A, B and C, exhibiting 1D microporous triangular shaped channels and based on different aromatic dicarboxylate ligands (1,4-BDC, 2,6-NDC and 4,4′-BPDC, respectively), were investigated by chromatographic breakthrough experiments regarding their ability to separate hexane isomers (nC6/2MP/3MP/23DMB/22DMB). Both single and equimolar multicomponent experiments were performed at the temperatures 343, 373, and 423 K and a total hydrocarbon pressure up to 50.0 kPa using the MIL-140B form. The elution order is similar to that of the normal boiling point of the compounds nC6 > 2MP > 3MP > 23DMB > 22DMB. It is noteworthy that this material enables separation of the hexane isomers by class, linear > mono-branched > di-branched, with a selectivity (linear + mono-branched isomers/di-branched isomers) up to 10 at 343 K, decreasing, however, as the temperature increases. Grand canonical Monte Carlo simulations were further performed to gain insight into the adsorption/separation mechanisms, highlighting the crucial need to consider a tiny tilting of the organic linkers for capturing the experimental observations. The impact of the pore size was finally assessed through the comparison with MIL-140A and MIL-140C, respectively, based on multicomponent experiments at 343 K. We evidenced a significant decrease of the selectivity (about 2) in both cases while the loadings were decreased or increased for MIL-140A and MIL-140C, respectively. Additionally, MIL-140C was demonstrated to exhibit an uncommon shift in the elution order occurring between nC6 and 3MP, 3MP being the last compound to saturate in the column.